Preparation of an N–S dual-doped black fungus porous carbon matrix and its application in high-performance Li–S batteries - Zhao, Liping; Zhao, Ye; Zhao, Lihe; Liu, Gang (Frontiers in Chemistry, 2023)
A nitrogen-sulfur dual-doped black fungus porous carbon (NS-FPC) matrix was prepared with natural black fungus as carbon source and cysteine as nitrogen-sulfur source. A black fungus based solution was obtained by hydrothermal treatment. After further carbonization activation and combined with sulfur process, the NS-FPC/S positive electrode materials were prepared. The uniform recombination of biomass carbon provides an efficient conductive framework for sulfur.The porous structure is conducive to the transport of electrolytes. Heteroatoms-doping can provide more active site. The structure and composition of the materials were carried out by X-ray diffraction (XRD) method. The electronic binding energy and bonding state was analyzed through X-ray photoelectron spectroscopy (XPS) test. The morphology was observed from scanning electron microscope (SEM) and transmission electron microscopy (TEM) detection. The specific surface area and pore size distribution were analyzed using N2 adsorption-desorption experiment.The sulfur loading was determined through thermogravimetric (TG) analysis. The electrochemical performance of NS-FPC/S in Li-S battery was systematically investigated. It shows that the NS-FPC/S electrode maintains more than 1000 mAh g -1 reversible capacity after 100 cycles at 0.2 C current density, with a capacity retention of 85 %. The cycle and rate performance are both far superior to traditional activated carbon materials.